Hoxa9 collaborates with E2A-PBX1 in mouse B cell leukemia in association with Flt3 activation and decrease of B cell gene expression - Hassawi, Mona; Shestakova, Elena A.; Fournier, Marilaine; Lebert-Ghali, Charles-Étienne; Vaisson, Gratianne; Frison, Héloïse; Sinnett, Daniel; Vidal, Ramon; Thompson, Alexander; Bijl, Janet J. (Wiley, 2014)
Background: The fusion protein E2A-PBX1 induces pediatric B cell leukemia in human. Previously, we reported oncogenic interactions between homeobox (Hox) genes and E2A-PBX1 in murine T cell leukemia. A proviral insertional mutagenesis screen with our E2A-PBX1 B cell leukemia mouse model identified Hoxa genes as potential collaborators to E2A-PBX1. Here we studied whether Hoxa9 could enhance E2A-PBX1 leukemogenesis. Results: We show that Hoxa9 confers a proliferative advantage to E2A-PBX1 B cells. Transplantation experiments with E2A-PBX1 transgenic B cells overexpressing Hoxa9 isolated from bone marrow chimeras showed that Hoxa9 accelerates the generation of E2A-PBX1 B cell leukemia, but Hoxa9 is unable to transform B cells alone. Quantitative-reverse transcriptase polymerase chain reaction analysis demonstrated a strong repression of B cell specific genes in these E2A-PBX1/Hoxa9 leukemias in addition to Flt3 activation, indicating inhibition of B cell differentiation in combination with enhanced proliferation. Overexpression of Hoxa9 in established E2A-PBX1 mouse leukemic B cells resulted in a growth advantage in vitro, which was also characterized by an enhanced expression of Flt3. Conclusions: we show for the first time that Hoxa9 collaborates with E2A-PBX1 in the oncogenic transformation of B cells in a mouse model that involves Flt3 signaling, which is potentially relevant to human disease.